Społeczna odpowiedzialność przedsiębiorstwa w kontekście polityki personalnej - Głuszek, Ewa (Corporate social responsibility in the context of HRM policy, 2006)
The author describes a new approach to social corporate responsibility and six major types of corporate social initiatives. Participation in those initiatives can have an impact on key performance factors, and the most important one is increased ability to attract, motivate and retain employees.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 206-215